MEDIKOLEGAL PENGOBATAN UNTUK DIRI SENDIRI (SWAMEDIKASI) SEBAGAI UPAYA MENYEMBUHKAN PENYAKIT - Sumartini Dewi (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2017)
It has become a habit of self-medication with non-prescription drugs done by most Indonesians. In the Regulation of the Minister of Health No. 924 / MENKES / PER / X / 1993 Regarding the Medication List of Pharmacies regulates certain hard drugs that pharmacists can give to people without a prescription. The purpose of the publication of Permenkes is to swamedikasi, a person can self- edicate rationally and supported by the pharmacy's mandatory drugs, although in general pharmacists can not sell hard drugs without a prescription, but there are certain hard drugs based on Permenkes may be sold without a doctor's prescription . The issue raised is how medikolegal swamedikasi in the perspective of healing disease? as well as how are the barriers and medicolegal swamedikasi solutions in the perspective of curing diseases? swamedikasi most places done in pharmacies, knowing drugs purchased through news media such as advertising the reason is the first attempt before treatment to health care facilities, swamedikasi actors get an explanation of doses and how to drink by pharmacist / clerk / drug seller, surveillance of swamedikasi drug use carried out with how to monitor / inspect pharmacies, the results obtained are frequent pharmacists are not in place at open pharmacy hours, selling OWA (Pharmacy Drug Compensation) without the presence of pharmacists and administrative violations. The obstacles are not yet optimal supervision from the government solution with counseling about the rule of law of drug delivery, the second barrier of the lack of awareness of drug sellers in pharmacies that do not fit the provisions of the solution by giving counseling to the owner of pharmacy facilities so as not to pursue Profit Oriented but pay attention to Patient Oriented, the third obstacle of lack of knowledge the swamediciator of the drug classes that the solution can buy is the government to increase socialization or counseling to the community about proper and responsible swamedication.